An exploration of mobile money transfer service adoption among Islamic bank customer in Somalia = Penerimaan perkhidmatan pemindahan wang mudah alih antara pelanggan bank Islam di Somalia - Suleiman, Dauud Mohamed; Hamdan, Hamdino (Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2018)
The world is changing rapidly due to technology, which is becoming an increasing necessity in the daily lives of people. Mobile Money Transfer Service (MMTS) is an alternative form of cash money that demonstrates the concept of electronic payment. Dahabshiil Bank International and Salam Somali Bank adopted MMTS in Somalia in partnership with a telecommunication company provider for MMTS. There has been no prior study conducted on the important factors affecting the adoption of MMTS among Islamic banking customers in Somalia. Based on the extended Theory of Technology Acceptance Model (TAM), perceived usefulness, perceived ease of use, perceived trust and perceived risk are used as predictors. The main objective of this study is to explore the customer acceptance on the important factors that influence the MMTS adoption among Islamic bank customers in Somalia. The target population of the study is Somali residents who use the MMTS and have bank accounts. This research, using statistical methods, collected data from 404 customers. The result of this study shows that the factors that influence the adoption of MMTS are perceived ease of use, perceived usefulness, perceived trust, which were found to be positive and significant while perceived risk was negative and significant.